Gendered Language in Advertising: A Critical Stylistic Perspective (Journal of the College of Basic Education, 2026)
This paper investigates how gender is linguistically constructed in advertising through the lens of Critical Stylistics. Drawing on Jeffries’ (2010) analytical tools and informed by Halliday’s transitivity model and Butler’s theory of gender performativity, the study explores how advertisements encode gendered ideologies through subtle linguistic choices. A purposive sample of ten gender-targeted advertisements from print and digital media was analyzed using stylistic tools such as naming and describing, transitivity, modality, and oppositional pairing. The findings reveal consistent patterns that align femininity with beauty, softness, and emotionality, while portraying masculinity in terms of power, action, and control. These portrayals are not arbitrary but ideologically driven, reinforcing traditional gender norms. However, a minority of the texts offer progressive alternatives, suggesting a potential shift in how gender is represented in advertising discourse. The study highlights the utility of Critical Stylistics in revealing hidden ideologies within everyday media and calls for more conscious language use in advertising to challenge gender stereotypes and promote diversity.